Penguatan Kompetensi Tenaga Kesehatan dalam Skrining Awal Gangguan Kesehatan Jiwa: Upaya Menuju Masyarakat Sehat di Puskesmas Bantur - Priasmoro, Dian Pitaloka; Asri, Yuni; Soebagijono (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Mental health disorders are a serious problem that requires early detection at the primary care level. Objective: This community service aims to improve the competency of Bantur Community Health Center health workers in early screening for mental health disorders. Method: The activity method includes Community Mental Health Nursing (CMHN)-based training, field practice, and pre-test and post-test evaluations. A total of 25 health workers consisting of nurses, midwives, dentists, medical records staff, and laboratory staff actively participated. Result: The results showed an increase in the average score from 65.2 to 88.4 after the training. Participants were able to apply screening skills and mental health education in the community. Conclusion: CMHN training is effective in improving knowledge and skills in early detection of mental disorders. Conclusion: Continuous training activities and integration of mental health services need to be expanded to support holistic and sustainable primary care.